2017
DOI: 10.3389/fpls.2017.00589
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Expression Patterns of CYC/TB1 Genes in Anacyclus: Phylogenetic Insights for Floral Symmetry Genes in Asteraceae

Abstract: Homologs of the CYC/TB1 gene family have been independently recruited many times across the eudicots to control aspects of floral symmetry The family Asteraceae exhibits the largest known diversification in this gene paralog family accompanied by a parallel morphological floral richness in its specialized head-like inflorescence. In Asteraceae, whether or not CYC/TB1 gene floral symmetry function is preserved along organismic and gene lineages is unknown. In this study, we used phylogenetic, structural and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…In Asteraceae, in addition to the organ identity genes, those controlling floral symmetry (CYC‐like genes) are also involved in sexual system expression (Yang et al., ). The diversification of CYC‐like genes that occurred in the Asteraceae (Bello et al., ) might have favored the acquisition of new functions for these genes in this family, such as the gynomonoecy expression linked to the radiate capitula. The hypothesis presented here is consistent with, and follows from, all these previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asteraceae, in addition to the organ identity genes, those controlling floral symmetry (CYC‐like genes) are also involved in sexual system expression (Yang et al., ). The diversification of CYC‐like genes that occurred in the Asteraceae (Bello et al., ) might have favored the acquisition of new functions for these genes in this family, such as the gynomonoecy expression linked to the radiate capitula. The hypothesis presented here is consistent with, and follows from, all these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some molecular genetic evidence supports the two loci model. The cycloidea family of genes (CYC genes) that control floral symmetry also regulate the expression of Asteraceae ray flowers (Gillies et al., ; Broholm et al., ; Kim et al., ; Chapman and Abbott, ; Bello et al., ). Recently, Yang et al.…”
mentioning
confidence: 99%
“…In snapdragon, CYC evolved as major effect copy (higher and broader dorsal-specific expression) and its duplicates DICH as helper function (Luo et al 1996 , 1999 ). Similarly, CYC tend to duplicate in most Angiosperm lineages with either both copies retain similar expression pattern (major/helper) or expressions become diversified thus under different selection pressures (Ree et al 2004 ; Chapman et al 2008 ; Bello et al 2017 ). In C. ramondioides , CrCYC1C and CrCYC1D both have sepal only expression but expression level of CrCYC1C is higher than CrCYC1D .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, reported that while one copy of CYC might have been positively selected after duplications, the other copy remained under purifying selection (Chapman et al, 2008 ; Zhong and Kellogg, 2015 ). Therefore, gene duplication of CYC is prevailing in many angiosperm lineages and perhaps diversifying selection on each copy may lead to their functional divergence (Bello et al, 2017 ). Indeed, duplicated CYC paralogs have been found differentiating their expression levels and patterns both spatially and temporally (Chapman et al, 2008 ; Jabbour et al, 2014 ; Zhong and Kellogg, 2015 ).…”
Section: Introductionmentioning
confidence: 99%